F2RL3 methylation in blood DNA is a strong predictor of mortality - Zhang, Yan (Int J Epidemiol, 2014)
Background: Smoking is a major cause of morbidity and mortality. Smoking-related epigenetic biomarkers may open new avenues to better quantify the adverse health effects of smoking, and to better understanding of the underlying mechanisms. We aimed to evaluate the clinical implications of F2RL3 methylation, a novel epigenetic biomarker of smoking exposure disclosed by recent genome-wide methylation studies. Methods: Blood DNA methylation at F2RL3 (also known as PAR-4) was quantified in baseline samples of 3588 participants aged 50–75 years in a large population-based prospective cohort study by MALDI-TOF mass spectrometry. Deaths were recorded during a median follow-up of 10.1 years. The associations of methylation intensity and of smoking with all-cause, cardiovascular, cancer and other mortality were assessed by Cox’s proportional hazards regression, controlling for potential confounding factors. Results: Lower methylation intensity at F2RL3 was strongly associated with mortality. After adjustment for multiple covariates including smoking, hazard ratios [95% confidence interval (CI)] for death from any cause, cardiovascular disease, cancer or other causes were 2.60 (95% CI, 1.81-3.74), 2.45 (95% CI, 1.28-4.68), 2.94 (95% CI, 1.68-5.14) and 2.39 (95% CI, 1.11-5.16), respectively, in subjects in the lowest quartile of methylation intensity compared with subjects in the highest quartile. The associations with mortality outcomes were much stronger among men than among women. In addition, strong positive associations of smoking with each of the outcomes were substantially weakened, and almost disappeared when controlling for F2RL3 methylation intensity. Conclusions: F2RL3 methylation is a strong predictor of mortality, including all-cause, cardiovascular, cancer and other mortality. Systemic adverse effects of smoking may be mediated by pathways associated with F2RL3 methylation.